Seeping plastics: Potentially harmful molecular fragments leaching out from microplastics during accelerated ageing in seawater. (1st July 2022) - Biale, Greta; La Nasa, Jacopo; Mattonai, Marco; Corti, Andrea; Castelvetro, Valter; Modugno, Francesca
Highlights: Accelerated ageing of reference microplastics in artificial seawater was performed. Solvent extraction of chemical species leached out in the water was developed. GC/MS qualitative and semi-quantitative analysis were performed. Leachates from plastic debris collected in natural environment were characterized. The toxicity of the leachates and formation pathways of the polymers were highlighted. Abstract: Microplastics are the particulate plastic debris found almost everywhere as environmental contaminants. They are not chemically stable persistent pollutants, but reactive materials. In fact, synthetic polymers exposed to the environment undergo chemical and physical degradation processes which lead not only to mechanical but also molecular fragmentation, releasing compounds that are potentially harmful for the environment and human health. We carried out accelerated photo-oxidative ageing of four reference microplastics (low- and high-density polyethylene, polypropylene, and polystyrene) directly in artificial seawater. We then made a characterization at the molecular level along with a quantification of the chemical species leached into water. Gas chromatography/mass spectrometry analyses performed after selective extraction and derivatization enabled us to identify more than 60 different compounds. Analysis of the leachates from the three polyolefins revealed that the main degradation products were mono- and dicarboxylic acids, along with linear and branched hydroxy acids. The highest amount of leached degradation species was observed for polystyrene, with benzoic acid and phenol derivatives as the most abundant, along with oligomeric styrene derivatives. The results from reference microplastics were then compared with those obtained by analyzing leachates in artificial seawater from aged plastic debris collected in a natural environment. The differences observed between the reference and the environmental plastic leachates mainly concerned the relative abundances of the chemical species detected, with the environmental samples showing higher amounts of dicarboxylic acids and oxidized species. Graphical abstract: Image, graphical abstract